The reality of e-learning from the viewpoint of students of private Jordanian universities in the northern region in light of the corona pandemic - Al-Harahsheh, Salem Hmood (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the reality of e-learning from the viewpoint of students of private Jordanian universities in the northern region in light of the Corona pandemic, and whether there are different expectations towards electronic education according to gender, specialization and cumulative rate, and the study sample consists of (294) male and female students. She uses the descriptive analytical approach, The results of the study showed that the advantages of e-learning in Jordanian private universities in the northern region from the students ’point of view in light of the Corona pandemic, came at a medium level and with an arithmetic average (3.40), and the efficiency of using education came at a high level, with an average of (3.43), while the negatives (Obstacles and Difficulties) E-learning came in a moderate degree, with an average of (3.03), and the results also showed that there were no statistically significant differences about the advantages of e-learning and about the efficiency of using e-learning according to the variable of specialization, and the presence of statistically significant differences in the dimension of the negatives of e-learning according to the gender variable. And in favor of females, and the existence of statistically significant differences in the dimension of the advantages of e-learning according to a variable Cumulative , and in favor of those with an acceptable variable Cumulative, The study recommended holding courses and workshops for students; To enlighten them about the importance of this system (e-learning), its benefits and importance, and how to use the Internet and applications related to e-learning, and to include courses related to e-learning for all students in Jordanian universities.
Keywords: e-learning; Universities; Corona Pandemic